Attenuation of quorum sensing controlled virulence factors and biofilm formation in Pseudomonas aeruginosa by pentacyclic triterpenes, betulin and betulinic acid. (May 2018) - Rajkumari, Jobina; Borkotoky, Subhomoi; Murali, Ayaluru; Suchiang, Kitlangki; Mohanty, Saswat Kumar; Busi, Siddhardha
Abstract: The production of virulence determinants and biofilm formation in numerous pathogens is regulated by the cell-density-dependent phenomenon, Quorum sensing (QS). The QS system in multidrug resistant opportunistic pathogen, P. aeruginosa constitutes of three main regulatory circuits namely Las, Rhl, and Pqs which are closely linked to its pathogenicity and establishment of chronic infections. In spite intensive antibiotic therapy, P. aeruginosa continue to be an important cause of nosocomial infections and also the major cause of mortality in Cystic Fibrosis patients with 80% of the adults suffering from chronic P. aeruginosa infection. Hence, targeting QS circuit offers an effective intervention to the ever increasing problem of drug resistant pathogens. In the present study, the pentacyclic triterpenes i.e. Betulin (BT) and Betulinic acid (BA) exhibited significant attenuation in production of QS-regulated virulence factors and biofilm formation in P. aeruginosa, at the sub-lethal concentration. The test compound remarkably interfered in initial stages of biofilm development by decreasing the exopolysaccharide production and cell surface hydrophobicity. Based on the in vivo studies, the test compounds notably enhanced the survival of Caenorhabditis elegans infected with P. aeruginosa . Furthermore, molecular docking analysis revealed that BT and BA can act as a strong competitive inhibitor for QS receptors, LasR and RhlR. The findings suggest that BT and BA can serve as potential anti-infectives in the controlling chronic infection of P. aeruginosa . Highlights: Efficacy of Betulin (BT) and Betulinic acid (BA) in attenuating quorum sensing (QS)-in P. aeruginosa was studied. A significant decrease in the biofilm formation was observed in P. aeruginosa with sub-MIC of BT and BA. The test compounds significantly enhanced the survival of C. elegans infected with P. aeruginosa, in vivo . The test compounds prevented the binding of the natural ligands to the QS receptors, LasR and RhlR.